The Facebook Paradox: Effects of Facebooking on Individuals’ Social Relationships and Psychological Well-Being - Hu, Xiaomeng; Kim, Andrew; Siwek, Nicholas; Wilder, David (Frontiers in Psychology, 2017)
Research suggests that Facebooking can be both beneficial and detrimental for users’ psychological well-being. The current study attempts to reconcile these seemingly mixed and inconsistent findings by unpacking the specific effects of Facebooking on users’ online-offline social relationship satisfaction and psychological well-being. Using structural equation modeling, pathways were examined between Facebook intensity, online-offline social relationship satisfaction, perceived social support, social interaction anxiety, and psychological well-being. Personality differences on each of those causal paths were also assessed. Employing a sample of 342 American university students, results indicated that intensive Facebooking was positively associated with users’ psychological well-being through online social relationship satisfaction, and simultaneously negatively linked to users’ psychological well-being through offline social relationship satisfaction. Multiple group analyses revealed that the linkage between perceived social support and psychological well-being was stronger for introverts than for extraverts. Our findings indicate that the benefits or detriments of Facebooking are contingent upon both personality characteristics and online-offline social contexts.